Improved estimates of conduction velocity distributions using single unit action potentials. Issue 6 (June 1981) - Milner, T E; Stein, R B; Gillespie, J; Hanley, B
Abstract : Single unit potentials were recorded from sural and medial gastrocnemius nerves. Action potential amplitude, integrated area and half-width (duration) were approximately proportional to conduction velocity, raised to the powers 1.5, 1 and -0.5 respectively with the sural nerve, and 2, 1.5 and -0.5 for the medial gastrocnemius nerve. These empirical relationships were applied to the computation of whole nerve conduction velocity distributions based on the relative number of single unit potentials of various conduction latencies required to reconstruct a recorded compound action potential. Conduction velocity distributions, which were converted to fibre diameter distributions, were in close agreement with the corresponding distributions determined histologically.